Disappearance of myocardial bridging of the left anterior descending coronary artery after inferior myocardial infarction - Bekir Serhat Yıldız; Fatma Esin; Yusuf Izzettin Alihanoğlu; Ismail Doğu Kılıç; Harun Evrengül (KARE Publishing, 2014)
Myocardial bridging (MB) is defined as the intramural course of a major epicardial coronary artery, and is mostly confined to the left ventricle and the left anterior descending coronary artery (LAD). MB is a common congenital abnormality of a coronary artery, and is usually thought to be a benign anatomical variant. Although rare, previous studies have reported that patients with MB may suffer from myocardial ischemia, myocardial infarction (MI), arrhythmias, and even sudden death. Therefore, the diagnosis and treatment of MB are both important. Since MB is congenital, its disappearance is unlikely. We here report a very rare case of disappearance of MB after inferior MI.